2010
DOI: 10.1111/j.1399-6576.2009.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Procedural pain of an ultrasound‐guided brachial plexus block: a comparison of axillary and infraclavicular approaches

Abstract: We did not find significant differences between the two approaches in procedural pain and patient's acceptance. The choice of approach may depend on the anaesthesiologist's experience and the patient's preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
1
30
0
1
Order By: Relevance
“…Twenty-nine studies compared US against another nerve localization method, 7-35 of which 10 were published since the first iteration of this article. [7][8][9][10][11][12]15,16,18,19 Seventeen studies compared 2 (or more) different US-guided approaches, [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] with 11 new articles published since August 2009. [36][37][38][39][40][41][42][43][44]46,49 The median Jadad score for included articles was 3.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine studies compared US against another nerve localization method, 7-35 of which 10 were published since the first iteration of this article. [7][8][9][10][11][12]15,16,18,19 Seventeen studies compared 2 (or more) different US-guided approaches, [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] with 11 new articles published since August 2009. [36][37][38][39][40][41][42][43][44]46,49 The median Jadad score for included articles was 3.…”
Section: Resultsmentioning
confidence: 99%
“…2). Nine trials used regional anaesthesia alone [7-9, 30, 33, 35, 36, 39, 40], one trial also used general anaesthesia [42], nine trials sedated with propofol [6,11,23,26,28,29,32,34,37] and six sedated with midazolam and an opioid [10,22,27,31,38,41].…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen trials compared different brachial plexus approaches: axillary vs infraclavicular [8,31,35,42]; axillary vs supraclavicular [38,39]; infraclavicular vs Figure 2 Risks of bias in seven methodological domains for each trial, categorised as: low (green); unclear (yellow); or high (red). supraclavicular [7,26,28,33,36,37,41]; and one trial compared the three approaches [6].…”
Section: Resultsmentioning
confidence: 99%
“…An investigation was performed with the primary aim to assess procedurerelated pain during block placement and look to recognize the cause(s) [26]. The authors compared procedural pain from patients randomized to either an axillary or infraclavicular block and results showed that the in-plane axillary approach took a longer time to perform and required more needle passes.…”
Section: Brachial Plexus Blockade: Single or Multiple Injection Sitesmentioning
confidence: 99%